GASING Method Training and Elementary Teachers’ Content Knowledge of Basic Arithmetic in West Manggarai, Indonesia - Yenni Natalina Buknoni; Turmudi Turmudi; Effy Mulyasari; Eva Puspitasari (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study examined the effectiveness of GASING (Gampang, Asyik, dan Menyenangkan) method training on elementary school teachers’ content knowledge of basic arithmetic operations, namely addition, subtraction, multiplication, and division, in West Manggarai Regency, East Nusa Tenggara, Indonesia. Methodology: A pre-experimental one-group pretest-posttest design was employed. Fifty-five elementary school teachers in West Manggarai Regency participated in a 10-day (80-hour) GASING training program. A content knowledge test (Cronbach's alpha = 0.89) was administered as the measurement instrument. Data were analyzed using the Wilcoxon signed-rank test, Hake’s normalized gain (N-gain), and Cohen's d, processed with SPSS version 26. Main Findings: Teachers’ content knowledge improved substantially following training, with mean scores rising from 31.00 to 72.09 out of 100, more than double the pretest level. This gain was statistically significant (Wilcoxon Z = −6.441, p < 0.001) and represented a very large practical effect (Cohen's d = 2.94), indicating the improvement was not only reliable but also substantively meaningful. Normalized gain analysis (N-gain = 0.59, medium category) showed that 96.4% of teachers achieved moderate-to-high learning gains, suggesting the training was effective across nearly the entire cohort rather than only for a subset of participants. Novelty/Originality of this study: This study extends the existing GASING literature, unlike prior studies that centered on student learning outcomes or general teacher motivation, this study contributes targeted evidence on teacher professional development in basic arithmetic instruction, offering a replicable, low-resource training model applicable to similarly under-resourced regions in eastern Indonesia.